2021
DOI: 10.1155/2021/7973356
|View full text |Cite
|
Sign up to set email alerts
|

Tooth- and Patient-Related Conditions May Influence Root Canal Treatment Indication

Abstract: Aim. To investigate predisposing aspects related to the indication for root canal treatment (RCT) at Dental Schools of Brazil. Methods. Data of 207 patients referred to endodontic treatment at undergraduate Dental Schools of Brazil were collected over a period of 8 months. Patient-related data included age, gender, first dental visit, tooth brushing frequency, number of remaining teeth, and previous endodontic treatment, and tooth-related information regarding number, type, and location in the mouth of teeth t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(51 reference statements)
1
0
0
Order By: Relevance
“…Moreover, higher proportion (54.4%) of the treatment was done on the right side of the dental arches, similar to a report by Osadolor et al 15 The first molar was found to be the most common tooth needing root canal treatment. This observation is similar to previous studies 21,22 but different to others 24,16 which found that the most frequently root canal treated teeth were the premolars and the central incisors, respectively. The first molar has been cited as the most caries-prone tooth in permanent dentition, perhaps due to its early exposure to the oral environment and its morphologic features being pitted and fissured, bringing plaque and caries formation.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, higher proportion (54.4%) of the treatment was done on the right side of the dental arches, similar to a report by Osadolor et al 15 The first molar was found to be the most common tooth needing root canal treatment. This observation is similar to previous studies 21,22 but different to others 24,16 which found that the most frequently root canal treated teeth were the premolars and the central incisors, respectively. The first molar has been cited as the most caries-prone tooth in permanent dentition, perhaps due to its early exposure to the oral environment and its morphologic features being pitted and fissured, bringing plaque and caries formation.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, little tenderness upon percussion, no sharp pain, and no radiographic radiolucency indicate asymptomatic irreversible pulpitis. Necrotic pulp is characterized by no sensitive response in the cold test [ 6 ].…”
Section: Introductionmentioning
confidence: 99%